The effects of persuasion in W.K. Tamsanqa's (1958) Buzani Kubawo and A.M. Mmango's (1964) UDike noCikizwa - Nozewu, Asithandile Esona (Stellenbosch : Stellenbosch University, 2018)
Thesis (MPhil)--Stellenbosch University, 2018.